Parasitos e comensais intestinais em pacientes neoplásicos submetidos à quimioterapia - Silva, Luciana Pereira [UNESP]; da Silva, Regildo Márcio Gonc̈alves [UNESP]; Fernandes, Natalia Amendola [UNESP]; de Oliveira, José Aparecido Alves (My University, 2011)
The objective of this study was to verify the prevalence of intestinal parasites and/or commensals in the neoplastic patients undergoing chemotherapy. Stool samples were analyzed by the method of Lutz (1919) and Rugai (1954), in triplicate. This work was composed of three groups, the first one (GI) formed by neoplastic patients that are not undergoing chemotherapy, the second (GII) comprised patients who were undergoing chemotherapy, and the third group (GIII) consisting of patients who completed chemotherapy. A total of 30 patients (GI-5, GII-18 and GIII-7) were screened at the Assis Regional Hospital of the Unified Health System of Assis, São Paulo. Additional information on antiparasitic treatment and tumor type were obtained by questionnaire. The positivity was 66.7% (20 cases) for intestinal parasites and/or commensals. The helminths were Ascaris lumbricoides (36.7%), Hookworms (20%) and Hymenolepis diminuta (3.3%). Among the highlights are protozoan Giardia lamblia (46.7%), Entamoeba coli (6.7%), E. histolytica /dispar (3.3%), Endolimax nana (3.3%) and Iodameba butschlii (3.3%). The high frequency of intestinal parasites and/or commensals in the neoplastic patients can be attributed to poor personal hygiene and lack of immunity to reinfection and poor knowledge of the prophylaxis of infection by protozoa and helminths. The results indicate the necessity of adopting a new criterion for neoplastic patients undergoing chemotherapy, primarily performing parasitological diagnosis, treatment and monitoring of cure of intestinal parasitic infections in this risk group.
Parasitic and intestinal commensals in the neoplastic patients undergoing chemotherapy
Keywords: Chemotherapy; Immunosuppression; Parasitic